A Critical Analysis of Decision Support Systems Research Revisited: The Rise of Design Science. (December 2014) - Arnott, David; Pervan, Graham
In 2005 the Journal of Information Technology article 'A critical analysis of decision support systems research' analyzed 1020 decision support systems (DSS) articles from 1990 to 2003. Since 2003 business intelligence (BI) and business analytics have gained popularity in practice. In theory and research the period since 2003 has seen a change in the decision-making theory orthodoxy and the codification and acceptance of design science. To investigate the changes in the DSS field, a number of expectations were derived from previous literature analyses. These expectations were assessed using bibliometric content analysis. The article sample to 2010 now includes 1466 articles from 16 journals. The analysis of the expectations yields mixed results for the DSS field. On the negative side, there has been an overall decline in DSS publishing, the relevance of DSS research published in journals to IT professionals has declined, and the rigor of DSS research designs has not improved. On the positive side, there has been improvement in relevance to managers, grant funding of DSS research has increased, there has been a positive shift in judgment and decision-making foundations, BI publishing has increased, and group support systems publishing has reduced to a more balanced level. An important result from the analysis of the last 7 years of DSS research is the significant increase in DSS design-science research (DSR) to almost half of published articles. It is clear from the analysis that DSS is undergoing a transition from a field based on statistical hypothesis testing and conceptual studies to one where DSR is the most popular method.